GDI Sprays with up to 200 MPa Fuel Pressure and Comparison of Diesel-like and Gasoline-Like Injector Designs - Lehnert, Bastian; Conrad, Chris; Wensing, Michael (SAE Technical Papers, 2020)
To address stricter emission limits, GDI develops to increased fuel pressure. Current gasoline injectors are already operating at a pressure of up to 35 MPa and an elevation is still promising lower particle emissions and increased efficiency. There have been only few studies of GDI sprays at pressures >50 MPa published. Contrary, in diesel engines injection pressure up to 250 MPa are common. GDI and diesel injector designs limit liquid penetration in different ways to avoid wall wetting, which has a negative impact on emissions in GDI combustion concepts. With elevated fuel pressure the question arises which design concept limits the penetration depth more effectively. To investigate the properties of high pressure sprays, a GDI injector (100 MPa max. fuel pressure) and an injector with diesel-like design are compared. High speed Shadowgraphy and Schlieren technique are used to gather information of liquid and vapor phase propagation. With Phase-Doppler-Anemometry (PDA) the diameter and the velocity of droplets in the sprays are recorded. Measurements are executed in a spray bomb with ambient pressure up to 4 MPa and ambient temperature up to 660 K. Results show that, increased fuel pressure lowers the mean and maximum diameter of the droplets. At the same time, considering ambient conditions, the spray penetration is not always higher at higher pressures, despite higher spray velocities. The injector design affects the penetration depth and the transition to the vapor phase, due to different rates of air entrainment. At higher fuel pressures the diesel design leads to faster vaporization, therefore the mixture formation and phase change are also faster, especially in high temperature ambient conditions. While a typical GDI design limits penetration more efficiently at moderate injection pressures and in low to moderate ambient conditions, the situation changes for very high injection pressure >50 MPa and late injection timing.
CRIS-Team Scopus Importer:2020-10-30